A methodology for ontological knowledge capture from databases - García-Sánchez, F.; Fernández-Breis, J.T.; Martínez-Bejar, R. (Інститут програмних систем НАН України, 2008)
The successful emergence of the Information and Communication Technologies (ICT) has contributed to the efficiency improvement in a number of economic sectors. However, some strategic economic sectors, such as construction, have not been targeted enough yet. Construction-related ICT solutions lack mechanisms to permit the effective integration of the whole supply chain. Semantic Web can tackle these issues. This paper presents a methodology for acquiring knowledge from construction-related databases. A domain ontology has been developed that contains the relevant concepts regarding supply management in the construction domain. The methodology basically consists of mapping the database content onto the ontology and a further this one’s population by applying a set of mapping rules. Успешное появление информационно-коммуникационных технологий (ИКТ) внесло свой вклад в повышение эффективности многих секторов экономики. Однако, некоторые стратегические экономические сектора, такие, как строительство, не были все же достаточно исследованы. Связанные со строительством решения ИКТ испытывают недостаток в механизмах, позволяющих разрешать проблемы эффективной интеграции полной цепочки поставки. Семантическая Сеть может заняться этими проблемами. Эта статья представляет методологию, позволяющую извлекать знание из баз данных, связанных со строительством . Была разработана онтология домена, содержащая релевантные понятия, касающиеся управления поставками в домене строительства. Методология в основном состоит из отображения содержания базы данных на онтологию и дальнейшего ее заполнения , применяя набор правил отображения .